Reducing depression level of diabetes mellitus patient by psychoeducation by means of poster - Yuniartika, Wachidah; Dwidiyanti, Meidiana; Mu’in, Muhammad (International Journal of Research in Medical Sciences, 2017)
Background: Diabetes Mellitus (DM) is a chronic, lifelong disease that requires continuous treatment and strict diet that could affect physical, psychological, and social function of an individual. Diabetes Mellitus patients tend to have chronic stress due to long period of emotional struggle that could lead to depression. One of the proven psychological interventions to treat depression is by psychoeducation. Methods: This was a quantitative study, with purposive sampling and pretest-posttest design with control group method. This study used two groups, which were intervention group (group with treatment) and control group. This study was conducted at the Baki public health center, Sukoharjo, Central Java, Indonesia, from April to May 2016. The total respondent was 40 persons with mild to moderate depression level. We assessed depression level by using Patient Health Questionaire (PHQ-9). Data analysis was calculated using paired t test, data normality test was calculated using Shapiro-Wilk statistical test. Results: This study showed that depression level for respondents in intervention group before intervention was in mild category, with the average value of 7.80, then after received psychoeducation therapy, the average value declined 3.60 points to 4.20 (no depression) and P value 0.000. In control group, the depression level was in mild category, with the average value of 8.15, these value decreased by 0.2 points to 7.98 (still in mild depression) after post test with P value 0.464. The depression level of Diabetes Mellitus patient who received psychoeducation declined significantly compared to the patient in control group. Conclusions: Psychoeducation intervention had significant effect on reducing depression level for Diabetes Mellitus patient.